Journal of Food Science and Technology Nepal (JFSTN): At a Glance - Dahal, Nawa Raj; Dawadi, Ganesh (Journal of Food Science and Technology Nepal, 2013)
Journal of Food Science and Technology Nepal (JFSTN) is one of the major publications of Nepal Food Scientists and Technologists (NEFOSTA). In the history of its 25 years from its formation in 1984, JFSTN had begun to publish from twenty years of age and at this moment; five issues of JFSTN (Volume 1, 2005 to Volume 5, 2009 as an annual basis) have been published. JFSTN includes five different types of papers i.e. Review articles, Research papers, Research notes, View points and Short Communications. Altogether one hundred and one articles of different types (Review articles 28, Research papers 48, Research notes 23, viewpoint 1 and short communication 1) are published in these five issues of JFSTN (12, 27, 20, 17 and 25 at issue 1 to 5 respectively). This article wishes to explore the information about the status and significance of JFSTN for the development of Food Technology Profession in Nepal. J. Food Sci. Technol. Nepal, Vol. 6 (122-129), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8274